Determination of workload, work facilities and communication on employee performance through job satisfaction in regional revenue agency of Karimun District - Dewi, Asmara; Indrawan, Mohamad Gita; Yanti, Sri (Goodwood Publishing, 2024)
Purpose: This study aims to determine and analyze the effect of workload, work facilities, and work environment on employee performance, with job satisfaction as a mediating variable at the Karimun Regency Regional Revenue Agency. Research Methodology: This study employed an associative causality design using a quantitative approach. Data were collected using questionnaires distributed to 102 respondents. Statistical analysis was conducted using SPSS and structural equation modeling-partial least squares (SEM-PLS) to test the direct and indirect relationships among variables. Results: The findings revealed that workload, work facilities, and communication each had a positive and significant direct effect on employee performance, with p-values of 0.041, 0.002, and 0.001, respectively. Job satisfaction also directly and significantly affected performance (p = 0.006). Although workload did not significantly influence job satisfaction (p = 0.065), work facilities (p = 0.003) and communication (p = 0.010) had significant effects. Mediation analysis showed that job satisfaction did not mediate the relationship between workload and performance (p = 0.553) but mediated the effect of work facilities (p = 0.003) and communication (p = 0.023) on performance. Conclusions: The study concludes that work facilities and communication play a stronger role in enhancing employee satisfaction and performance than workload, with job satisfaction acting as an important mediator. Limitations: This study was limited to one agency with a relatively small sample size, potentially constraining the generalizability of the findings. Contribution: This study contributes to the public sector human resource management literature by demonstrating how job satisfaction mediates workplace factors and performance. Practically, the findings provide insights for policymakers to improve employee outcomes through better facilities and communication strategie.